Parametric study of a reinforced concrete footbridge strengthened by a layer of UHPFRC - Petr Kněž; Milan Holý; Jiří Kolísko (Acta Polytechnica CTU Proceedings, 2025)
This paper deals with the presentation of a parametric study of the strengthening of a reinforced concrete footbridge with a layer of reinforced UHPFRC on its upper surface. In order to increase its load carrying capacity, stiffness and durability, the design of strengthening with 50 mm thick UHPFRC layer was carried out. The geometry of the analyzed structure is based on the real structure. The parametric study solves its strengthening by considering different support options of the structure and its degradation. The design and assessment was carried out in the form of nonlinear numerical analysis using the FEM in Atena 3D.